Exploring the distribution and correlates of future self-continuity in a large, nationally representative sample - Hal E. Hershfield; Craig I. Brimhall; Susan Kerbel (Judgment and Decision Making)
Many people struggle to make tradeoffs between present wants and future wishes, resulting in the tendency to overly discount the value of future rewards. To explain such behavior, past work has pointed to future self-continuity or the perceived connection between a person’s current and future selves. Yet, most of this past work has been conducted on small-to-medium size convenience samples, and as such, little is known regarding the population-level statistics of future self-continuity or how its link to important financial health variables like saving behavior and financial well-being play out in a nationally representative sample. Here, we use a nationally representative sample of over 6,000 Americans to investigate the generalizability of future self-continuity and its connection to financial outcomes such as savings behavior and global financial well-being. We also examine the strength of these associations in the face of a host of other relevant constructs. Overall, this research replicates and extends existing work on the relationship between future self-continuity and financial decision-making among a representative population, and sheds further insight on its potential implications for interventions aimed at enhancing long-term financial well-being.